Comparative Study Between Single Layer and Double Layer Graft Technique in Tympanoplasty for Subtotal Tympanic Membrane Perforation - Aziz, Ahmed Abdel Rahman Abdel; Hafez, Montaser Abdel Salam; Mahmoud, Ashraf Gamal; Hamad, AbdelMoneim H. (International Archives of Otorhinolaryngology, 2023)
Introduction Tympanoplasty is the main treatment of mucosal type of chronic suppurative otitis media.Objective The aim of the present study was to compare clinical outcomes in terms of healing and audiological outcomes of two groups. The authors used single layer graft (perichondrium with cartilage island) graft in one group and double layer grafts (perichondrium cartilage island composite plus temporalis fascia) were used in the second group.Methods Forty patients complained of chronic suppurative otitis media safe type with subtotal perforation subdivided into two groups. The first group author used single-layer perichondrium with cartilage island graft (composite graft) while in the second group authors used double graft in the form of perichondrium/cartilage island (composite graft) plus temporalis fascia.Results There was no significant difference in the mean Air bone gap (ABG) between pre- and post-operative audiometry in subjects who had single layer tympanoplasty. There was a significant difference in the mean ABG between pre- and postoperative audiometry in subjects who had double layer tympanoplasty. There was a significant difference in in the mean ABG differences between subjects who had single layer tympanoplasty and double layer tympanoplasty. Also, there was a significant difference in the healing of the tympanic membrane between subjects who had single layer tympanoplasty and double layer tympanoplasty.Conclusion Tympanoplasty by double graft (temporalis fascia and tragal cartilage/perichondrium) achieved a considerable improvement in healing of the tympanic membrane ™ with lower risk for residual perforation or graft rejection.
Keywords: otitis media; ear diseases; hearing disorders